Immunomodulatory potential of mesenchymal stromal cell-derived extracellular vesicles in chondrocyte inflammation - Ossendorff, Robert; Grad, Sibylle; Tertel, Tobias; Wirtz, Dieter C.; Giebel, Bernd; Börger, Verena; Schildberg, Frank A. (Frontiers in Immunology, 2023)
Osteoarthritis (OA) affects a large percentage of the population worldwide. Current surgical and nonsurgical concepts for treating OA only result in symptom-modifying effects. However, there is no disease-modifying therapy available. Extracellular vesicles released by mesenchymal stem/stromal cells (MSC-EV) are promising agents to positively influence joint homeostasis in the osteoarthritic surroundings. This pilot study aimed to investigate the effect of characterized MSC-EVs on chondrogenesis in a 3D chondrocyte inflammation model with the pro-inflammatory cytokine TNFα.Bovine articular chondrocytes were expanded and transferred into pellet culture at passage 3. TNFα, human MSC-EV preparations (MSC-EV batches 41.5-EVi1 and 84-EVi), EVs from human platelet lysate (hPL4-EV), or the combination of TNFα and EVs were supplemented. To assess the effect of MSC-EVs in the chondrocyte inflammation model after 14 days, DNA, glycosaminoglycan (GAG), total collagen, IL-6, and NO release were quantified, and gene expression of anabolic (COL-II, aggrecan, COMP, and PRG-4), catabolic (MMP-3, MMP-13, ADAMTS-4 and ADAMTS-5), dedifferentiation (COL-I), hypertrophy (COL-X, VEGF), and inflammatory (IL-8) markers were analyzed; histological evaluation was performed using safranin O/Fast Green staining and immunohistochemistry of COL I and II. For statistical evaluation, nonparametric tests were chosen with a significance level of p < 0.05. TNFα supplementation resulted in catabolic stimulation with increased levels of NO and IL-6, upregulation of catabolic gene expression, and downregulation of anabolic markers. These findings were supported by a decrease in matrix differentiation (COL-II). Supplementation of EVs resulted in an upregulation of the chondrogenic marker PRG-4. All MSC-EV preparations significantly increased GAG retention per pellet. In contrast, catabolic markers and IL-8 expression were upregulated by 41.5-EVi1. Regarding protein levels, IL-6 and NO release were increased by 41.5-EVi1. Histologic and immunohistochemical evaluations indicated a higher differentiation potential of chondrocytes treated with 84-EVi.MSC-EVs can positively influence chondrocyte matrix production in pro-inflammatory surroundings, but can also stimulate inflammation. In this study MSC-EV 41.5-EVi1 supplementation increased chondrocyte inflammation, whereas MSC-84-EVi supplementation resulted a higher chondrogenic potential of chondrocytes in 3D pellet culture. In summary, the selected MSC-EVs exhibited promising chondrogenic effects indicating their significant potential for the treatment of OA; however, the functional heterogeneity in MSC-EV preparations has to be solved.